ANALISIS KETERAMPILAN BERBICARA BAHASA INGGRIS MAHASISWA KEPERAWATAN UNIVERSITAS MOHAMMAD NATSIR DALAM MENGGUNAKAN METODE PEMBELAJARAN ROLE PLAY - Fadli, Noval; Afdaleni, Afdaleni; Destri, Nentien; Pratama, Engla Rati (Ensiklopedia of Journal, 2025)
This study aims to analyze the English-speaking skills of homicide students after implementing the role play learning method. Effective communication skills in English are crucial for nurses amidst global demands and interactions with patients from various backgrounds. The role play method is believed to be able to provide a safe environment simulation to practice speaking skills. This descriptive qualitative study involved 35 3rd semester students at Mohammad Natsir University Bukittinggi. Data were collected through participant observation during role play sessions, role play video recordings, and interviews with students. The results showed that role play significantly improved students' fluency (fluency), accuracy (accuracy), pronunciation (pronunciation), and interpersonal communication skills (interpersonal communication skills). Students showed increased confidence in speaking and the ability to adapt language to the clinical context. However, challenges related to specific medical understanding and early anxiety management still need to be addressed. This study authorizes a more intensive integration of role play in the homicide English curriculum to equip students with relevant communication skills in the workplace.Keywords: Role Play, Speaking Skills, English, Nursing Students.